JAPAN FOREIGN POLICY IN COOPERATION WITH INDIA THROUGH ASIA AFRICA GROWTH CORRIDOR (AAGC) - Nur Afrillia; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Economic cooperation is one of the interests of every country that wants to maintain its position in the international political system. Japan and India are no exception. In this study, showed the reasons behind Japan's interest in agreeing to cooperate with India to build partnerships through the Asia Africa Growth Corridor (AAGC) in 2017. AAGC reflects the convergence of bottom-up and top- down rocesses, which is in the interest of Japanese businesses in using India as astepping stone to Africa and a desire to provide a geopolitical alternative to the region. These two dimensions need to be considered in analyzing the beginning of the collaboration. This research is theoretically built using the perspective of neoliberalism, and is supported by foreign policy theory. The formulation of all arguments, data, facts, and theoretical frameworks in this study uses a qualitative explanation method. This study also uses the nation-state as a level of analysis. The results of this study are that there are three sources of foreign policy that underlie Japan to realize the AAGC as the fulfillment of its country's interests. First, systemic sources explained that the balancing of China's Belt and Road Initiative (BRI) strategy was through Japan's Free and Open Indo-Pacific Strategy. Second, societal sources see India as a stepping stone to the African market. Third,the government source is Shinzo Abe's proactive foreign relations strategy towardsIndia. Keywords: AAGC, Belt and Road Initiative, Free and Open Indo-Pacific, foreign policy